Small colon impaction outbreak and associated risk factors in horses at the Onderstepoort Veterinary Academic Hospital, South Africa in 2021 - Smit, Yolandi (University of Pretoria, 2024)
Dissertation (MMedVet (Equine Surgery))--University of Pretoria, 2024.